ЛОГОМЕТРИЧЕСКИЙ МЕТОД АНАЛИЗА СОСТАВА СУСПЕНЗИЙ - Киреев Д.С.; Белоглазов И.Н.; Эль-Салим С.З. (My University, 2006)
Логометрический метод, рекомендованный металлургическим факультетом Санкт-Петербургского государственного горного института позволяет решить проблему анализа концентрации взвешенных частиц в дисперсных средах и концентрации истинных растворов и повысить эффективность контроля процессов в горной и металлургической промышленности без излишнего усложнения аналитической системы.

This report covers the problem of analysis of the concentration of suspension particles in dispersed mediums and the concentration of components in pure solutions. The logometric method recommended by the metallurgical department of Saint-Petersburg mining institute enables to solve this problem and to increase the efficiency of controlling processes in mining and metallurgical industry without complication of analytic system.
Keywords: (669+54):681.518.52